Improving healthcare for Aboriginal Australians through effective engagement between community and health services. Issue 1 (December 2016) - Durey, Angela; McEvoy, Suzanne; Swift-Otero, Val; Taylor, Kate; Katzenellenbogen, Judith; Bessarab, Dawn
Abstract Background Effectively addressing health disparities between Aboriginal and non-Aboriginal Australians is long overdue. Health services engaging Aboriginal communities in designing and delivering healthcare is one way to tackle the issue. This paper presents findings from evaluating a unique strategy of community engagement between local Aboriginal people and health providers across five districts in Perth, Western Australia. Local Aboriginal community members formed District Aboriginal Health Action Groups (DAHAGs) to collaborate with health providers in designing culturally-responsive healthcare. The purpose of the strategy was to improve local health service delivery for Aboriginal Australians. Methods The evaluation aimed to identify whether the Aboriginal community considered the community engagement strategy effective in identifying their health service needs, translating them to action by local health services and increasing their trust in these health services. Participants were recruited using purposive sampling. Qualitative data was collected from Aboriginal participants and health service providers using semi-structured interviews or yarning circles that were recorded, transcribed and independently analysed by two senior non-Aboriginal researchers. Responses were coded for key themes, further analysed for similarities and differences between districts and cross-checked by the senior lead Aboriginal researcher to avoid bias and establish reliability in interpreting the data. Three ethics committees approved conducting the evaluation. Results Findings from 60 participants suggested the engagement process was effective: it was driven and owned by the Aboriginal community, captured a broad range of views and increased Aboriginal community participation in decisions about their healthcare. It built community capacity through regular community forums and established DAHAGs comprising local Aboriginal community members and health service representatives who met quarterly and were supported by the Aboriginal Health Team at the local Population Health Unit. Participants reported health services improved in community and hospital settings, leading to increased access and trust in local health services. Conclusion The evaluation concluded that this process of actively engaging the Aboriginal community in decisions about their health care was a key element in improving local health services, increasing Aboriginal people's trust and access to care.